Model design for code generation for C# and SQL Server - Rojas Torres, Juan M. (2022)
Currently there are tools that generate source code automatically. We propose a source code generation architecture focused on the 3-layer architecture, additionally we build a source code generation tool. The Tool allows to load a database schema and from this it generates the source code for the SQL Server and C# language, we use an .xls file to import or export the database schema. We have used 5 code generation requirements and their database schemas for the test, obtaining as a result the generation of source code without errors. Carrying out the time analysis, our model generates 6,998 lines of code per second, in total we have generated 13,283 lines of source code in 1472 milliseconds that correspond to 5 requirements for generating source code with their respective databases.